PELAKSANAAN GADAI EMAS (RAHN) PADA PERBANKAN SYARIAH DI PT. BANK NAGARI SYARIAH KANTOR CABANG PEMBANTU BATUSANGKAR - lewis, Denince; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Financial intermediaries (banks) is the largest bank, where the bank is supporting infrastructure is vital to support the economy. According to its type, the bank is divided into two types namely conventional banks and Islamic banks, the Islamic banking business activities translates into Islamic banking products. One of them is the pledge of gold (Rahn). But in the gold pawning maintenance costs should not be adjusted based on the weight of gold. Philosophical foundation based DSN Fatwa No.25/DSN-MUI/III/2002 concerning Rahn, namely the cost of maintenance should not be a large according to mortgage loans granted. The purpose of this study was to answer the problems in this study, namely: first, the implementation of the gold pledge (Rahn) by Nagari Bank Syariah Capem Batusangkar; secondly, the barriers that are found in the implementation of the pledge of gold (Rahn) in the village bank branch Batusanggkar sharia either from the bank or the customer; and thirdly, efforts to resolve the problems that occur in the process of implementation of the pledge of gold (Rahn) at Nagari Bank Syariah Capem Batusangkar.From the research it can be concluded that the implementation of the pledge of gold at Nagari Bank Syariah Batusanggkar their Capem not agree as to the costs of maintenance with DSN Fatwa No.2/DSN-MUI/ III/2002 About Rahn. Many obstacles found in its execution is delayed customers pay mortgages, the lack of personnel and facing a competitor from another financial institution. Efforts to resolve the problems in the implementation of the pledge of gold is to be good communications between the customer and the bank, the increase of employees in the field of gold pawn, and improve services, and promote products that exist in Islamic banking.Keywords: Gold Pawn, Rahn, Nagari Bank Syariah Capem Batusangkar